Glucose homeostasis in the euryhaline crab Cytograpsus angulatus : Effects of the salinity in the amylase, maltase and sucrase activities in the hepatopancreas and in the carbohydrate reserves in different tissues - Asaro, Antonela (2018)
We studied the existence, biochemical characteristics and response to different environmental salinities of amylase, maltase and sucrase activity in the intertidal euryhaline crab Cyrtograpsus angulatus (Dana, 1852) along with the response to distinct salinities of glycogen and free glucose content in storage organs. Amylase, maltase and sucrase activities were kept over a broad range of pH and temperature and exhibited Michaelis–Menten kinetics. Zymography showed the existence of two amylase forms in crabs exposed to 35 (osmoconformation) and low (6–10 psu; hyper-regulation) or high (40 psu) (hypo-regulation) salinities. Carbohydrases activity in the hepatopancreas and glycemia were not affected in crab exposed to different environmental salinities. In 6 and 40 psu, the glycogen content in anterior gills was lower than in 35 psu. In 6, 10 and 40 psu, glycogen concentration in hepatopancreas, muscle and posterior gills were similar to that in 35 psu. Free glucose concentration in chela muscle was higher in 6 and 40 psu than in 35 psu. The existence and biochemical characteristics of carbohydrases activity and the adjustments in concentration of glycogen in anterior gills and free glucose in chela muscle suggests the ability to perform complete hydrolysis of glycogenic substrates and to keep glucose homeostasis in relation to acclimation to different salinity conditions.